Uncanny Beloveds and the Return of the Repressed - Maya Petrovich (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: In the course of Ottoman history, a long-standing alliance with the Giray house allowed for military cooperation; yet, classical Ottomans writers held a paradoxical posture toward Crimean Tatars. One current of tradition praised them as handsome and skilled warriors, but a purported betrayal by Tatars during the battle against Tīmūr in 1402 evolved into a recurrent motif of Ottoman historiography, justifying the ambivalence which the courtly elites felt toward Chinggisids and the northern steppe. The catastrophic period of Tatar expulsion and their resettlement in Ottoman territories in the 1850s and 1860s gradually led Ottoman writers toward a reassessment of the Crimea, projecting a new romantic image of Tatars as heroic, embattled and loyal fellow Muslims. Finally, in the twentieth century, new paradoxes arose, marking the formerly nomadic Tatars as closely related to the Black Sea and Anatolia, and yet also distinctly exotic and “Asiatic.” The study demonstrates that complex cyclical processes of fluidity and crystallization were always operative within Ottoman perceptions and their definitions of non-Ottoman peoples, including the Tatars.